The Effect of Information Quality and Promotional Media on Satisfaction with BSI Mobile Banking (Student Case Study FAI UMSU) - Fiya Oktavia; Alfi Amalia (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to determine the effect of information quality and promotional media on satisfaction with BSI mobile banking (case study of FAI UMSU students). This study uses a quantitative method with random sampling of 84 samples. The data analysis technique used in this study is quantitative analysis, namely the process of analyzing data in the form of numbers by means of statistical calculations to measure the quality of information and promotional media on satisfaction with BSI mobile banking. The results of the study show that simultaneously, information quality (X1) and promotional media (X2) have a significant effect on BSI mobile banking user satisfaction (Y).